Life cycle approaches in human resources management and their impact on competitiveness: A comprehensive bibliometric study - Kusumah, Yudi; Permana, Johar; Rahyasih, Yayah; Sururi, Sururi (Indonesian Research Journal in Education |IRJE|, 2025)
This study explores the intellectual structure of life cycle approaches in human resource management (HRM) and their impact on organizational competitiveness through a comprehensive bibliometric analysis. A total of seven Scopus-indexed publications were analyzed using performance analysis and science mapping tools, specifically VOSviewer. Findings reveal an emerging and fragmented research field characterized by dispersed authorship and globally distributed contributions. Key themes identified include competency development, performance optimization, sustainability, and digital transformation, highlighting the interdisciplinary integration of HRM with engineering, environmental management, and technological innovation. The analysis also indicates limited theoretical consolidation, with no dominant authors or institutions. The study concludes that HRM life cycle approaches hold significant potential for enhancing organizational competitiveness but require further theoretical integration and empirical research. Recommendations emphasize developing integrated HRM life cycle models, strengthening alignment with digital and sustainability goals, and promoting international and cross-industry research collaborations.